Synergistic Impact of Alpha-Fetoprotein and Tumor Burden on Long-Term Outcomes Following Curative-Intent Resection of Hepatocellular Carcinoma - Tsilimigras, DI (2021)
Introduction: The prognostic role of tumor burden score (TBS) relative to pre-operative α -fetoprotein (AFP) levels among patients undergoing curative-intent resection of HCC has not been examined. Methods: Patients who underwent curative-intent resection of HCC between 2000 and 2017 were identified from a multi-institutional database. The impact of TBS on overall survival (OS) and cumulative recurrence relative to serum AFP levels was assessed. Results: Among 898 patients, 233 (25.9%) patients had low TBS, 572 (63.7%) had medium TBS and 93 (10.4%) had high TBS. Both TBS (5-year OS; low TBS: 76.9%, medium TBS: 60.9%, high TBS: 39.1%) and AFP (>400 ng/mL vs. <400 ng/mL: 48.5% vs. 66.1%) were strong predictors of outcomes (both p < 0.001). Lower TBS was associated with better OS among patients with both low (5-year OS, low-medium TBS: 68.0% vs. high TBS: 47.7%, p < 0.001) and high AFP levels (5-year OS, low-medium TBS: 53.7% vs. high TBS: not reached, p < 0.001). Patients with low-medium TBS/high AFP had worse OS compared with individuals with low-medium TBS/low AFP (5-year OS, 53.7% vs. 68.0%, p = 0.003). Similarly, patients with high TBS/high AFP had worse outcomes compared with patients with high TBS/low AFP (5-year OS, not reached vs. 47.7%, p = 0.015). Patients with high TBS/low AFP and low TBS/high AFP had comparable outcomes (5-year OS, 47.7% vs. 53.7%, p = 0.24). The positive predictive value of certain TBS groups relative to the risk of early recurrence and 5-year mortality after HCC resection increased with higher AFP levels. Conclusion: Both TBS and serum AFP were important predictors of prognosis among patients with resectable HCC. Serum AFP and TBS had a synergistic impact on prognosis following HCC resection with higher serum AFP predicting worse outcomes among patients with HCC of a certain TBS class.